Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.5606/tgkdc.dergisi.2021.22340
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for incisional hernia after abdominal aortic aneurysm and aortic occlusive disease surgery

Abstract: Background: This study aims to investigate incisional hernia incidence and risk factors after abdominal aortic aneurysm and aortic occlusive disease surgery via a midline laparotomy. Methods: A total of 110 patients (66 males, 44 females; mean age: 69.3±8.8 years; range, 36 to 88 years) who underwent open elective surgery for aortoiliac occlusive diseases or abdominal aortic aneurysm between January 2005 and December 2016 were retrospectively analyzed. Both patient groups were compared in terms of surgical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…7,8,21 In a study comparing AAA and AOD repair, a BMI of 25 kg/m 2 or higher was found to be an independent risk factor for IH. 10 Obesity is associated with a higher intraabdominal pressure and wound-healing complications as a consequence of decreased vascularity of adipose tissue. The synthesis of mature collagen is impaired in hypoxic wounds, resulting in weakened tissue formation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…7,8,21 In a study comparing AAA and AOD repair, a BMI of 25 kg/m 2 or higher was found to be an independent risk factor for IH. 10 Obesity is associated with a higher intraabdominal pressure and wound-healing complications as a consequence of decreased vascularity of adipose tissue. The synthesis of mature collagen is impaired in hypoxic wounds, resulting in weakened tissue formation.…”
Section: Discussionmentioning
confidence: 99%
“…Although collagen tissue composition, genetic mutation, clear biological indicator, or significant relationship between risk factors have not yet been fully elucidated in AAA formation and abdominal wall hernias, it is believed that an underlying imbalance between collagen Type 1 and 3 is the common point in the pathophysiology of these conditions. 2,7,10,20 There are a few studies in the literature that compare the groups in terms of IH development between AAA and AOD, and it has been reported that the AAA group has a greater IH rate, up to a median of 5-fold increased risk. 7,8,21 In a study comparing AAA and AOD repair, a BMI of 25 kg/m 2 or higher was found to be an independent risk factor for IH.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations